Evaluation of watershed management interventions on biomass carbon sequestration and stakeholders’ perception about watershed condition improvement (case study: Dehchenashk sub-watershed, Chehl Chai watershed) - Zeinab Karimi; Vahedberdi Sheikh; Amir Sadoddin; Naghmeh Mobarghaee Dinan (علوم محیطی)
Introduction: Increasing the atmospheric carbon dioxide concentration is a major cause of climate change that has led to degradation in natural ecosystems and incidence of various environmental problems such as imbalances in hydrologic, nutrients, and carbon cycles in nature. Land surface cover, which has an important role in carbon sequestration, has been strongly influenced by human activities and gradually degraded over time and created a number of challenges in the behavior of watersheds. Therefore, worldwide rehabilitation and restoration of watersheds through the implementation of a variety of mechanical and biological measures have been considered by policymakers, managers, and technical experts. For instance, various watershed management projects (tree sapling, permanent forage cultivation, and terracing) have been implemented with the participation of stakeholders to improve conditions in the Dehchenashk sub-watershed of the Chehl-Chai watershed, where is considered as the most critically degraded watershed of the Golestan Province, northeastern Iran. Therefore, this research was carried out to evaluate the effects of land cover and various management measures on the amount of carbon sequestration in surface soil layer through a comparative analysis between two sub-watersheds of Dehchenashk (treatment) and Chamanie-bala (control).Material and methods: In the present study, the effect of management measures on carbon sequestration in areas under management measures (treatment) and types of land use (forest, croplands, and orchards) was studied. The croplands and orchards as controls and terracing and tree saplings activities (biological measures) as the treatment measures were compared in terms of carbon sequestration. Sampling was conducted using randomly selected plots along the defined transects. Within each plot, above-ground biomass was measured for crops and trees. Also, the effect of management measures on improving land cover and reducing soil erosion from viewpoints of the local stakeholders was carried out using the questionnaire survey.Results and discussion: The results showed that the average of biomass carbon sequestration (ton/ha) in both treatment and control sub-watersheds in dense (5.10 and 4.91), low-density (4.98 and 4.80), and degraded forests (4.27, 95 and 95) was more than walnut (Juglans regia) (3.08 and 2.85) and apple (Malus pumila) (2.21 and 2.00) orchards, and croplands cultivated with alfalfa (Medicago sativa) (1.55 and 1.50), wheat (Triticum aestivum) (1.40 and 1.32), lentil (Lens culinaris) (1.38 and 1.30), and barley (Hordeum vulgare) (1.26 and 1.19), respectively. Regarding biological practices carried out in the treatment sub-watershed, the average carbon sequestration in walnut orchards (2.72) was higher than pear (Pyrus communis) (1.88) and cherry (Cerasus avium) (1.66) orchards and terraced lands cultivated with alfalfa (1.65), wheat (1.50) and lentil (1.40). Also, statistical comparison using T-test between high density, low-density, and degraded forests and apple orchards and barley croplands showed no statistically significant difference at 5% level. The amount of sequestrated biomass carbon in walnut, pear, and cherry orchards and terraced lands cultivated with lentil, alfalfa, and wheat showed significant differences in comparison with the control lands. Moreover, the evaluation of viewpoints of the local stakeholders on the effect of management measures implemented in the Deh-Chanashk sub-watershed, indicated that they believe that the implemented watershed management practices have played a significant role in improving the sub-watershed condition in terms of land cover, soil stabilization, and soil erosion reduction.Conclusion: Therefore, among the watershed management measures undertaken, extending the orchard plantation, particularly walnut plantation, to croplands on the steep slopes is recommended as a high priority management option across the study region due to higher ability to carbon sequestration as well as soil erosion prevention.